Water Scarcity: A Case Study of Poompuhar Village, Ariyalai East in Jaffna District - Raam, R.; Srikanthan, S. (University of Jaffna, 2021)
Water scarcity is a major social problem at present and it is a major factor in creating other social problems. Clean drinking water is essential for maintaining the quality and health of human life. Access to clean drinking water is a fundamental human right at present as it is seen as one of the basic necessities of life. Water scarcity is, therefore, seen as the biggest challenge to the social development of the village. This study attempts to analyze the socio-economic issues resulting from water scarcity in the Poompuhar village of Ariyalai East, Jaffna District. Jaffna is an area that relies on groundwater resources. This study is a descriptive study based on a qualitative approach. Fieldwork spanning the period of August to October 2020 inform the primary data for the study. Case study method is used as a principal tool for collecting data along with key informant interviews. Records from the Grama Niladari and the Divisional Secretariat are used as secondary data sources. Primary data collected through purposive sampling method focuses on the theme of causes and socio-economic effects of water scarcity in the study area and secondary data express the nature and reality of the study village. There is a risk of water scarcity in Jaffna peninsula. Groundwater pollution as a result of increased agricultural fertilizers, human activities, variations in rainfall, soil erosion, depletion of water bodies such as ponds, fields, and rapid deforestation exacerbate water scarcity in Jaffna. The socio-economic implications of water scarcity in this village can be ascertained by analyzing the case studies done in the area. The current economic status of the village dwellers and the scarcity of water in the village further affect their socio-economic status. People spend a portion of their daily income to buy water while they spend more time and human resources to source water from distant places. It is worth noting here that, sometimes, internal conflicts arise between family members and neighbors as they source water from public wells or pipes. Even though efforts have been made by the government and Non- governmental Organizations alleviate the water shortage in Poompuhar, they are not sufficient. In this context, this study suggests that it is important that the government implement awareness programmes and projects to ensure the accessibility of water during drought seasons.
Keywords: Case study; Socio-economic issues; Water scarcity